English Education Department Students’ Difficulties in Translating English News Report - Nurlaila Nurlaila; Andi Irlina (PANYONARA: Journal of English Education, 2021)
Different language systems between English and Indonesian cause difficulties in communication, both written and oral. This case can be solved with translation. This research aims to find about types of translation difficulties in translating English news reports encountered by the fourth semester of English Education Department students of Tarbiyah and Teacher Training Faculty at UIN Antasari Banjarmasin. This research is a qualitative descriptive research by analyzing the text of the news report entitled "London is the Best Destination in the World in the 2019 Trip Advisors Travellers' Choice Awards," published on 29 March 2019 at 00.48:00 a.m translated into Bahasa Indonesia by involving 50 of the students. The number of the students are the participants taken by using purposive sampling. The writers collect the written documents due to translating the text of the English News Report by the students, analyze the words, phrases, and sentences to find the students' difficulties based on Hartono's theory. There are four difficulties the writers found in this study. The difficulties are lexical, grammatical, stylistic, and cultural difficulties.